Study of Electronic and Dielectric Properties of Magnesium Phosphide - Omkar, H. S.; Sreepad, H. R. (Asian Journal of Science and Applied Technology, 2018)
First-principles calculations based on Density Functional Theory have been done on Magnesium phosphide. Its cubic unit cell has been simulated. Band gap in case of this material comes out to be 0.5eV. This value is in the range exhibited by semiconducting materials. Dielectric constant and Polarizability of the material have been computed. The value of dielectric constant comes out to be 51.9 along all the three axes. The polarizability values are found to be 46.7 (Å)3 along all the three axes. Phonon modes at gamma point in the material range from 0 cm-1 to 452 cm-1.